Direct imaging of DNA in living cells reveals the dynamics of chromosome formation. - Manders, E; Kimura, H; Cook, P (1999)
Individual chromosomes are not directly visible within the interphase nuclei of most somatic cells; they can only be seen during mitosis. We have developed a method that allows DNA strands to be observed directly in living cells, and we use it to analyze how mitotic chromosomes form. A fluorescent analogue (e.g., Cy5-dUTP) of the natural precursor, thymidine triphosphate, is introduced into cells, which are then grown on the heated stage of a confocal microscope. The analogue is incorporated by the endogenous enzymes into DNA. As the mechanisms for recognizing and removing the unusual residues do not prevent subsequent progress around the cell cycle, the now fluorescent DNA strands can be followed as they assemble into chromosomes, and segregate to daughters and granddaughters. Movies of such strands in living cells suggest that chromosome axes follow simple recognizable paths through their territories during G2 phase, and that late replicating regions maintain their relative positions as prophase chromosomes form. Quantitative analysis confirms that individual regions move little during this stage of chromosome condensation. As a result, the gross structure of an interphase chromosome territory is directly related to that of the prophase chromosome.